A comparative study of depression and associated risk factors among elderly inmates of old age homes and community of Rajkot: A Gujarati version of the geriatric depression scale-short form (GDS-G) - Dipeshkumar D Zalavadiya; Anupam Banerjee; Ankit M Sheth; Matib Rangoonwala; Aarohi Mitra; Amiruddin M Kadri (Wolters Kluwer Medknow Publications, 2017)
Background: The prevalence of depression among elderly people varies across different setups such as old age homes (OAHs), community, and medical clinics. Aims: The aim of this study was to compare the epidemiological factors pertaining to depression among elderly residents of OAHs and community, using a new Gujarati version of the Geriatric Depression Scale-Short Form (GDS-G). Settings and Design: A cross-sectional, epidemiological study conducted in an urban setup of Western India. Materials and Methods: All the eligible 88 elderly residents of all the six OAHs and 180 elderly residents from the same city were administered a pretested semistructured questionnaire having the GDS-G form. Statistical Analysis: Descriptive statistics, odds ratio, Spearman's rank correlation test. Results: The elderly of OAHs were more depressed compared to those of community (odds ratio = 1.84; 95% confidence interval = 1.09-3.06). Older age, females, weaker family ties, economic maladies, poorer self-perception of health status, presence of chronic ailments, absence of recreational activity, lack of prayers, impaired sleep, history of addiction emerged as the predictors of depression in both the setups. More health complaints and a later self-perception of visit to a doctor were found among the depressed than the nondepressed in both the setups. Conclusions: Depressive symptoms were quite high among the elderly in both the setups. Special attention should be given toward health checkups of depressed persons in the OAH and improvement of family ties among depressed persons of the community.